Exploring Novel Emerging Therapeutic Strategies for Parkinson’s Disease: A Narrative Review - Kulkarni, Vishal; Sai Kumari, R T; Muchandi, Sanjunath Satteppa; Nyamagoud, Sanatkumar Bharamu; Nanjappaiah, H M; Hooli, Vishwanath Jagadevappa; Tadkal, Sangamesh Sharanbasappa; Bali, Prasad Nijaguni (International Journal of Pharmaceutical Investigation, 2026)
Parkinson's Disease (PD) is a common neurodegenerative disorder. It is defined by a progressive loss of dopamine neurons in the substantia nigra pars compacta and neurodegeneration, which eventually results in a decrease in dopamine levels. This review provides an overview of PD. Parkinson's disease patients exhibit both non-motor symptoms like depression and anxiety as well as motor symptoms including bradykinesia, tremor and rigidity. PD involves Lewy body formation, dopamine neuron death and molecular pathways with α-synuclein clumping. Current PD management focuses on relieving motor symptoms through dopamine medications, glutamateblocking and surgery. However, non-motor symptoms require additional medications. This literature review also explores innovative treatment approaches like Aiming for α-Syn Aggregation, enhancing autophagy and promoting neuroprotection. It stops bad proteins from forming, blocks harmful genes and boosts the body's cleaning systems. There's also a focus on creating treatments that protect nerve cells. Some are channel blockers; others encourage cell response. Iron binders are used too. Inflammation in the brain is another focus. This is done through enzyme control and tweaking certain cell responses.
Keywords: Autophagy; Neurodegeneration; Neuroinflammation; Neuroprotection; Parkinson’s disease; α-synuclein aggregation.